Case Report: Ruptured Gastroduodenal Artery Aneurysm Post Pancreaticoduodenectomy - Abdul Rahman M. Sibiany; Abdulelah M. Alhawsawi; Reda A. Jamjoom; Ghada N. Enani (Journal of King Abdulaziz University: Medical Sciences, 2023)
Delayed arterial hemorrhage following pancreaticoduodenectomy is a rare complication, yet serious, that is associated with high mortality rate. Ruptured gastroduodenal aneurysm is one of the causes of upper gastrointestinal hemorrhage that requires quick identification and management to prevent further morbidities and mortality. Up-to-date, there is no consensus on the surgical management of ruptured visceral aneurysm. The surgical treatment of this condition varies according to the patient’s clinical status and the health care center expertise. This report, presents our own experience of the management of ruptured gastroduodenal aneurysm with endovascular and surgical methods.